Analysis of the Threat of Social Conflict between Local Communities and Immigrants in the Capital Region of the Indonesian Archipelago - Setiawan, Rio; Sucitra, I Gusti Ngurah Bagus (Security Intelligence Terrorism Journal (SITJ), 2025)
This article aims to examine the potential for social conflict between local communities and immigrants in the Indonesian Capital City (IKN) as a result of social, cultural, and economic inequality. Using a qualitative approach, data were collected through interviews, observations, and documentation studies. The results of the study indicate that social exclusion, disparities in facilities, and lack of communication between communities are the primary triggers of conflict. This study emphasizes the importance of early detection and intelligence strategies in mitigating conflicts that can disrupt national stability. This article aims to examine the potential for social conflict between local communities and immigrants in the Indonesian Capital City (IKN) as a result of social, cultural, and economic inequality. Using a qualitative approach, data were collected through interviews, observations, and documentation studies. The results of the study indicate that social exclusion, disparities in facilities, and lack of communication between communities are the primary triggers of conflict. This study emphasizes the importance of early detection and intelligence strategies in mitigating conflicts that can disrupt national stability.